Letters of Vaclav Jan Tomasek from the Morawetz Collection - Vojteskova, Jana (Musicologica Olomucensia, 2022)
The article deals with the letters of Vaclav Jan Krtitel Tomasek from the Morawetz Collection, housed in the National Museum - Czech Museum of Music. In a critical edition, it publishes and comments on the letters Tomasek addressed to the publishers Ambrosius Kuhnel, Carl Friedrich Peters, and Immanuel Guttentag, as well as to the poet and editor Rudolph Hirsch, Tomasek's pupil Alexander Dreyschock and an unnamed (probably Amelia Illaire to Berlin). The edition also includes an appraisal of the compositions of Josef Zvonar and Tomasek's request for an increase in his annual rent, addressed to Count George Franz August Buquoy in 1829. For the first time, a letter by Johann Wolfgang Goethe, the original of which is considered lost by the current edition of Goethe's correspondence, is published here according to the original.
Keywords: Jiri Frantisek August Buquoy; Alexander Dreyschock; Johann Wolfgang Goethe; Immanuel Guttentag; Rudolph Hirsch; Amelie Illaire; Ambrosius Kuhnel; Morawetz Collection; National Museum - Czech Museum of Music; Carl Friedrich Peters; Vaclav Jan Krtitel Tomasek; Josef Zvonar